Solution-coated barriers for organic electronics - Channa, Iftikhar Ahmed; Distler, Andreas; Brabec, Christoph; Egelhaaf, Hans-Joachim (Organic Flexible Electronics, 2021)
This chapter provides a review on solution processed barriers for flexible organic electronics. After elaborating on the necessity for encapsulation of organic devices by describing the degradation mechanisms caused by oxygen and water, the state of the art of vacuum-deposited barriers is briefly addressed as it presently defines the benchmark of barrier technology. Subsequently, the fundamentals of permeation of gases through barriers and the characterization methods for barrier performance are described. The main part of the chapter gives an overview of the material systems used for manufacturing solution-processed barriers. We start with the methods relying on reducing diffusion and solubility coefficients of oxygen and water in barrier films. Subsequently, barriers based on tortuosity and barriers based on covering substrates with layers of zero or very low permeability are described. Finally, the role of getters is elucidated. The chapter is concluded with highlighting some of the present challenges in the field of solution processed flexible barriers.<br
Keywords: Flexible barriers; flexible electronics; flexible packaging; organic photovoltaics; organic light emitting diodes; OLED; OPV; OFET; device lifetime; accelerated ageing